Dinamika Perkembangan Hukum Islam pada masa Dinasti Abbasiyah - Rheny Windi Nabila; Nabila Annisa Hasibuan; Sepia Walandari; Dinda Nurul Amalia; M. Dwi Azwar (Yayasan Dar Arrisyah Indonesia, 2023)
Abstract : This article aims as a tool to explore the development of Islamic law starting from the formation of the Abbasid dynasty until the collapsea nd decline of the Abbasid government. In this era, the heyday of ment in the fields of law and politics, especially its achievements, puta n icon of enthusiasm and experience in world civilization today. The development of the Abbasid civilization was also inseparable from the attention of just law enforcement as a driving force for the development oflaw, especially Islamic law at that time. The research technique used uses qualitative research methods from a historical approach and collects data obtained from books, articles, journals and many more. This scientific work notes that there are several histories and legal practices that became the development of Islamic law during the Abbasid dynasty. such as the formation of diwans, judicial bodies such as the judiciary and the prosecutor's office. Developments in certain periods, the orderliness of the legal system, the flow and formation of the justice system which was formed in detail with the fuqoha.